2010
DOI: 10.20429/ijsotl.2010.040212
|View full text |Cite
|
Sign up to set email alerts
|

Designing Learning Environments to Foster Affective Learning: Comparison of Classroom to Blended Learning

Abstract: Affective learning is a key dimension of health professional education and involves teaching topics such as empathy or grief that impact student attitudes and beliefs to prepare them to be novice practitioners. The move in higher education toward online and blended learning (a mix of online and traditional, classroombased learning) disrupts traditional approaches to teaching professional affect, which is heavily reliant on instructor modeling. This paper documents insight into the redesign process of a course,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 5 publications
0
26
0
Order By: Relevance
“…Also Schaber et al [43] added that proved that both classroom and blended learning formats are effective in enhancing learner's perceived understanding of affective content, although blended learning was proved more effective than classroom learning.…”
Section: Second Partmentioning
confidence: 99%
“…Also Schaber et al [43] added that proved that both classroom and blended learning formats are effective in enhancing learner's perceived understanding of affective content, although blended learning was proved more effective than classroom learning.…”
Section: Second Partmentioning
confidence: 99%
“…As we continue to invert our instruction, we have come to realize that doing so is more about the process of learning and how best to structure learning experiences to support students rather than a focus on technology. Schaber and colleagues () noted, “A successful learning environment is community‐centered, because a cohort of learners provides the support, motivation, and challenge to foster growth (Wenger, )” (p. 3). Similarly, Bergmann and Sams () argued, “Flipping the classroom is more about a mindset: redirecting attention away from the teacher and putting attention on the learner and the learning” (p. 11).…”
Section: Resultsmentioning
confidence: 99%
“…Nell and Wilkinson () also reported that what worked best in a blended course was not only the improved contact between the students and the instructor but also the immediate feedback that students received from the instructor. Furthermore, research has suggested that engagement in socially structured communities of practice with high levels of collaboration and feedback foster deeper levels of knowledge construction and often result in improved student learning (Akyol & Garrison, ; Alonso, Lopez, Manrique, & Vines, ; Schaber, Wilcox, Whiteside, Marsh, & Brooks, ). An increased focus on small‐group work during class plus online communication increased opportunities to develop communities of practice both outside and during class.…”
Section: Research On Blended and Inverted Instructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Develop is make or realize quizioner design that was created previously [10] [3] and the implementation is to implement or deploy questionnaires that have been made previously to the object of research or student. Here are the questions quizioner which will be given to students: After making as many as 20 questions on quizioner, the next step is the selection of the sample, the quizioner multiply and spread to some predetermined Students, Students will be given a few clues about the workmanship and given time to work.…”
Section: Develop and Implementationmentioning
confidence: 99%